Analysis of Problems in the Implementation of Elections in Districts or Villages - Rasji Rasji; Viane Patricia; Sanny Nuyessy Putri (CV. Rayyan Dwi Bharata, 2023)
General elections, hereinafter referred to as elections, have the means of popular sovereignty to elect members of the People's Representative Council, members of the Regional Representatives Council, President and Vice President, and to elect members of the Regional People's Representative Council which are carried out directly, publicly, freely, confidentially, honestly and fairly in the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Any choice is very prone to various violations and even fraud. Indicators that show the reasons for this problem are not only in the organizers, but also in the behavior of competitors. The intended Indonesian citizens are the original Indonesian people/nation and people of other nations who are legalized by law as citizens. Any choice is very vulnerable to various violations and even cheating. One of the violations that we often face is the abuse of the right to vote. General elections are considered to be the earliest stage of various series of democratic constitutional life. Law Number 7 of the 2017 Election clarifies various criminal provisions against violations and/or fraud in the administration of elections. So that elections are the driving force behind the mechanism of the Indonesian political system. Until now, elections are still considered as an important state event. This is because elections involve all the people directly.